Changes in the policy of the MIA of the USR SSR regarding the Ukrainian national liberation movement in march-june 1953 - V. A. Grechenko (Bulletin of Kharkiv National University of Internal Affairs)
The article examines the evolution of the policy of the Ministry of Internal Affairs of Ukraine headed by P. Ya. Meshyk regarding the Ukrainian national liberation movement in March-June 1953. This historical period was chosen by the author because after the death of the long-term leader of the USSR, Y. Stalin, certain changes in the international and domestic policy of the state began to take place, known in historical literature as the “Beria thaw”. During this period, the struggle against the OUN–UPA took on slightly different forms and methods. She became less cruel and brutal, less senseless, although this did not change her essence. As before, the goal of this struggle remained the elimination of the anti-Soviet underground, but it began to be done in a more sophisticated way. In the very first directive of the new minister, it was about canceling some Chekist-military operations, that is, about reducing their number and streamlining their organization. Some measures were taken regarding the new Ukrainianization of higher education institutions in Lviv. As of the beginning of 1953, only 114 of the 527 subjects taught at the Lviv Higher Secondary School were taught in Ukrainian. The situation was the same with the national composition of teachers at educational institutions. In the management of 12 higher educational institutions of Lviv, there was not a single director from among the local intelligentsia. Out of 45 deans of faculties, one is local, out of 286 heads of departments, 38 are local. Out of a total of 1,721 professors and teachers of 12 universities, only 327 were from the local intelligentsia. As a result of the armed confrontation with the OUN in the western regions of Ukraine in the period from 1944 to 1953, 153,259 people were killed, 103,003 people were arrested, 65,895 families, a total of 203,737 people, were evicted from the western regions of the Ukrainian SSR as “bandit aids”. P. Meshik managed to stay in the position of Minister of Internal Affairs for only three months, and many of his plans, which were, to a certain extent, reformist in nature, were not destined to be implemented.